1994
DOI: 10.1111/j.1432-1033.1994.tb19927.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of phospholipase C‐β2 by recombinant guanine‐nucleotide‐binding protein βγ dimers produced in a baculovirus/insect cell expression system

Abstract: Recombinant wild-type plyi dimers of signal-transducing guanine nucleotide-binding proteins (G proteins) and plyl dimers carrying a mutation known to block y-subunit isoprenylation (p1ylC71S) were expressed in baculovirus-infected insect cells. Both wild-type and mutant p,yl dimers were found in soluble fractions of infected cells upon subcellular fractionation. Anion exchange chromatographic and metabolic-radiolabeling studies revealed that the soluble plyl preparation contained approximately equal amounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 64 publications
3
50
0
Order By: Relevance
“…The dynamic equilibrium may be critical to the biochemical activity of the proteins since the interaction of the prenylated proteins with other macromolecules may be significantly affected by the methylation state of the adjacent −COOH group. This is perhaps more substantial based on the fact that the isoprenyl group of proteins such as the G-protein γ subunits are essential for their coupling of receptor-derived signals to such effector enzymes as the adenylyl cyclases and phospholipase Cβ2 [2,4,5]. Furthermore, an isoprenyl-binding site has been identified using solution NMR on Rho dissociation inhibitor [6].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic equilibrium may be critical to the biochemical activity of the proteins since the interaction of the prenylated proteins with other macromolecules may be significantly affected by the methylation state of the adjacent −COOH group. This is perhaps more substantial based on the fact that the isoprenyl group of proteins such as the G-protein γ subunits are essential for their coupling of receptor-derived signals to such effector enzymes as the adenylyl cyclases and phospholipase Cβ2 [2,4,5]. Furthermore, an isoprenyl-binding site has been identified using solution NMR on Rho dissociation inhibitor [6].…”
Section: Introductionmentioning
confidence: 99%
“…Farnesylcysteine analogs mimic the carboxy-termini of signal-transducing proteins ( y subunits of heterotrimeric G proteins or low-molecular-mass G proteins) and may thus elicit cellular responses by perturbation of interactions of these proteins with specific docking sites on diverse cellular components (IniguezLluhi et al, 1992;Dietrich et al, 1994;Kisselev et al, 1994;van Biesen et al, 1995). Cellular receptors that may be involved in specific interactions with prenylated termini include G-protein-coupled receptors (Kisselev et al, 1994;Sheer and Gierschik, 1995), PLCP (Dietrich et al, 1994) adenylate cyclase (Iniguez-Lluhi et al, 1992) n subunits of G proteins (IniguezLluhi et al, 1992;Higgins and Casey, 1994) and rhodopsin kinase (Premont et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular receptors that may be involved in specific interactions with prenylated termini include G-protein-coupled receptors (Kisselev et al, 1994;Sheer and Gierschik, 1995), PLCP (Dietrich et al, 1994) adenylate cyclase (Iniguez-Lluhi et al, 1992) n subunits of G proteins (IniguezLluhi et al, 1992;Higgins and Casey, 1994) and rhodopsin kinase (Premont et al, 1995). Blockade or simulation of these interactions by prenylcysteine analogs might in principle account for inhibition or activation of signals transmitted by the prenyl-receptor proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a mutant cDNA encoding a ␥ subunit lacking the essential cysteine residue required for isoprenylation resulted in a shift of the ␤␥ complex to the cytosol and prevented the increase in cellular inositol phosphates. Furthermore, the purification of ␤␥ dimers from baculovirus transfected insect cells has shown that only C-terminally modified ␥ subunits confer PLC␤2-activating function on ␤␥ complexes (35), suggesting that the isoprenylation and carboxyl methylation of ␥ subunits may be important for both membrane location and functionality of the complex. However, the extent of membrane insertion of G␤␥ is unlikely to explain the marked differences between lipid substrates in terms of the cooperativity observed and the extent of activation of PI 3-kinase.…”
Section: Figmentioning
confidence: 99%